Analisis Faktor-Faktor Yang Mempengaruhi Pengelolaan Alokasi Dana Desa (Studi Pada Kecamatan Penawartama Kabupaten Tulang Bawang) - Muhammad Luthfi; Eka Sariningsih; Ferri Muzzakki (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2018)
Abstract, This researched was purposed to analyze the factors that influence the management of theallocation of village funds. These factors include planning, implementation, accountability, andcompetence of human resources in the District Penawartama Tulang Bawang District. The sample ofthis research is 7 villages through purposive sampling method. Results of data analysis were testedusing SmartPls. The results showed that planning, implementation, responsibility, and competence ofhuman resources have an effect on the management of village fund allocation.